Māori University success: what helps and hinders qualification completion. (June 2017) - Theodore, Reremoana; Gollop, Megan; Tustin, Karen; Taylor, Nicola; Kiro, Cynthia; Taumoepeau, Mele; Kokaua, Jesse; Hunter, Jackie; Poulton, Richie
Māori (Indigenous New Zealand) university graduates are role models for educational success and are critical for the social and economic wellbeing of Māori whānau (extended family) and communities. In this study, Māori graduates ( N = 626) from all eight New Zealand universities participated in the Graduate Longitudinal Study New Zealand between July and December 2011. They were asked to describe factors that they found helpful or challenging to the completion of their qualifications. Graduates described a range of external (e.g. family), institutional (e.g. academic support), and student or personal (e.g. persistence) factors. Describing the experiences of Māori graduates can provide a blueprint for future indigenous success by building an evidence base of the factors that may promote indigenous higher educational achievement in New Zealand and internationally.